Meta‐analysis of the relationship between quality management practices and firm performance—implications for quality management theory development - Nair, Anand (Journal of Operations Management, 2006)
AbstractQuality management (QM) has received a high degree of attention in extant literature. Several research papers attribute superior firm performance to adoption of QM practices. The availability of a large number of research papers that investigate the impact of QM practices on performance provide an ideal setting for theory extension and refinement using meta‐analysis techniques. In this paper a meta‐analytic study is presented that fulfills two objectives. First, the paper formalizes performance implications of adopting QM practices and present hypothesized relationship between QM practices and performance. Second, a meta‐analysis of correlation (Hunter and Schmidt, 1990) approach is used to examine the empirical research in QM to determine which QM practices are positively related to improved performance. The study also examines the presence of moderating factors in the association between QM practices and performance. The results support many hypothesized relationships and also point towards the presence of moderating factors in almost all QM practice–performance relationships. A discussion of the findings is presented and directions for further development of QM theory are proposed.